Leadership Learning Partnerships: Self‐Authored Leadership through the Learning Partnerships Model. Issue 168 (30th November 2020) - Chunoo, Vivechkanand S.
Abstract: In this chapter, the author folds the learning partnerships model into leadership learning experiences for students' self‐authored leadership and offers practical guidance for leadership educators seeking to develop leaders who are authentically empowered agents of change.